2013
DOI: 10.1097/mbc.0b013e32835e98da
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume in patients with obstructive sleep apnea syndrome and its relationship with cardiovascular diseases

Abstract: Obstructive sleep apnea syndrome (OSAS) is an independent risk factor for the development of cardiovascular events and hypertension. Mean platelet volume (MPV), an indicator of platelet activation and aggregation, is closely related with cardiovascular diseases (CVDs). We aimed to show the relationship between OSAS and MPV with CVD. The medical records of 205 patients who were admitted to the sleep study were evaluated. OSAS was diagnosed by polysomnography if the apnea-hypopnea index (AHI) was greater than 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 32 publications
2
52
0
5
Order By: Relevance
“…Elevated cardiovascular disease incidence in OSAS might be due to impaired hypercoagulation and elevated plated activation observed in these patients. [5] In OSAS, platelets possibly become active through three mechanisms. [6] First, night hypoxemias and recurring wake ups result in sympathetic system activation characterized by epinephrine and norepinephrine increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated cardiovascular disease incidence in OSAS might be due to impaired hypercoagulation and elevated plated activation observed in these patients. [5] In OSAS, platelets possibly become active through three mechanisms. [6] First, night hypoxemias and recurring wake ups result in sympathetic system activation characterized by epinephrine and norepinephrine increase.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, platelet activation and aggregation have been reported to increase in patients with OSAS. [5,6] Mean platelet volume (MPV) is a parameter used as an indicator of platelet activation. Larger platelets are more reactive than normal-sized ones and have higher prothrombotic potentials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 These factors may contribute to the association between MPV and hypertension. When participants were stratified by platelet count, the highest MPV was significantly associated with an increased incidence of hypertension.…”
Section: Mpv and Hypertension L Gang Et Almentioning
confidence: 99%
“…In many studies, platelet activation and aggregation have been reported to increase in patients with OSAS. 12,13 Mean platelet volume (MPV) is a parameter used as an indicator of platelet activation. Larger platelets are more reactive than normal-sized ones and have higher prothrombotic potentials.…”
Section: Discussionmentioning
confidence: 99%